Superconducting and Graphene-based Devices - Giubileo, Filippo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue reprint aims to collect new or improved ideas to exploit superconducting materials, as well as graphene, towards achieving innovative devices, either at a small scale, as well as at a large scale. Several potential applications of graphene are enhanced by the possibility to modify its surface to introduce a non-zero bandgap, to tune adhesion and/or hydrophobicity/hydrophilicity, etc. These surface properties are crucial to the realization of graphene-based devices. Papers demonstrating graphene and/or superconducting devices, device processing, characterization, and applications, are particularly welcomed. Topics in this Special Issue include, but are not limited to: Graphene devices Graphene based heterostructures Superconducting interfaces Superconducting devices Electronic, optical, photonic and magnetic properties Surface and interfacial characterization techniques Device integration and fabrication